Premature drug release of polymeric micelles and its effects on tumor targeting - Miller, Tobias; Breyer, Sandra; van Colen, Gwenaelle; Mier, Walter; Haberkorn, Uwe; Geissler, Simon; Voss, Senta; Weigandt, Markus; Goepferich, Achim (International journal of pharmaceutics, 2013)
Based on the enhanced permeability and retention (EPR) effect, nanoparticles are believed to accumulate in tumors. In this conjunction, the stability of drug encapsulation is assumed to be sufficient. For clarification purposes, PEGylated poly-(d,l-lactic acid) (PEG-PDLLA) micelles which incorporated the hydrophobic model drug dechloro-4-iodo-fenofibrate (IFF) were investigated. H2N-PEG-PDLLA was synthesized, coupled to 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid (DOTA) and labeled with 111-indium. From this polymeric species, mixed micelles with H3CO-PEG-PDLLA were prepared which encapsulated the 125-iodine or 131-iodine labeled drug IFF. Bioimaging and biodistribution experiments in healthy and AR42J-tumor bearing mice were carried out to quantify the uptake of the drug and its carrier in single organs. As a result, upon injection of this system, a rapid dissociation of the polymeric carrier and the incorporated drug (<10min post inj.) was revealed. Regardless of the premature release, the drug showed an enhanced tumor accumulation compared to the polymeric carrier. In conclusion, the self-assembling system allowed for successful solubilization of the hydrophobic drug by physical incorporation into micelles whereas the tumor targeting properties of the drug delivery system could not be sufficiently shown.
Gesehen am 25.05.2021